Persepsi Keluarga Tentang Cara Merawat Orang Dengan Gangguan Jiwa Di Poli Klinik Rumah Sakit Jiwa Tampan Provinsi Riau - Isnaniar; Norlita, Wiwik; Solekhati, Maratus (Fakultas MIPA dan Kesehatan, Universitas Muhammadiyah Riau, 2022)
Mental disorders are behavioral deviations due to emotions,thoughts, feelings, motivations, desires, which cannot be achieved so that sufferers cannot control their behavior and emotions so that they interfere in the life process.Perception is all processes of selecting, organizing and interpreting input information, sensations received through sight, feeling, hearing, smell and touch to produce meaning. To find out the family's perception of how to care for people with mental disorders. This type of research is descriptive. This research was conducted on 13 to 20 September 2021 and 03 to 10 October 2021 at the Poli Clinic of the Tampan Mental Hospital Pekanbaru, Riau Province. The population in this study was 17,853 people with the number of research respondents used was 70 people. The sampling technique used is theaccidental sampling technique, namely by taking respondents in the polyclinic of the handsome mental hospital. The instrument used in this study was a questionnaire sheet using the Likert scale, namely choosing one of four alternativeanswers that were adapted to the subject's circumstances. Shows the family's perception of how to treat people with mental disorders in the polyclinic of the handsome mental hospital, Pekanbaru, Riau province, with a positive category of 36 respondents (51.4%) and a negative category of 34 respondents (48.6%). Family perceptions about how to care for people with mental disorders obtained positive perceptions, where patients must be supported by their families for regular treatment at the hospital, so that in this way the family obtains sufficient information about the treatment of mental disorders